1979
DOI: 10.1099/00221287-114-2-277
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Double Conidiation Mutants of Aspergillus nidulans

Abstract: A series of strains, doubly mutant at conidiation loci, have been made. The phenotypes of these strains reflected the epistasy of earlier blocking mutants over later ones and confirmed the order of gene sequence predicted from the phenotypes of single mutants. Oligosporogenous mutants gave complex interactions, especially between brl and med mutants.These results indicated that (i) gene action overlapped in time, (ii) several parts of the conidial apparatus were interchangeable and (iii) nuclei leaving the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
5

Year Published

1986
1986
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 6 publications
(2 reference statements)
0
16
0
5
Order By: Relevance
“…At the morphological level, brlA mutations are epistatic to abaA and wetA mutations and abaA mutations are epistatic to wetA mutations (9). We determined that these epistatic relationships were manifested at the molecular level.…”
Section: Resultsmentioning
confidence: 99%
“…At the morphological level, brlA mutations are epistatic to abaA and wetA mutations and abaA mutations are epistatic to wetA mutations (9). We determined that these epistatic relationships were manifested at the molecular level.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the conidiophore morphology of stuA mutants is a function of incorrect temporal or spatial expression of phialide-specific genes such as abaA. The result is a failure to differentiate metulae or phialides, and conidia are produced from buds on the conidiophore vesicle (Martinelli 1979;Miller et al 1991). Strain UI49 was constructed to test this hypothesis.…”
Section: Stua Is Required For Correct Spatial Expression Of the Abaa mentioning
confidence: 99%
“…They affect patterns of cell differentiation and the spatial organization of the conidiophore (Clutterbuck 1969;Martinelli 1979;Miller et al 1991J. stuA null mutants have greatly shortened conidiophores and lack normal metulae and phialides.…”
mentioning
confidence: 99%
See 2 more Smart Citations